The Influence of Financial Literacy and Risk Tolerance on Investment Decisions for Millennial Generation Civil Servants (PNS) - Sekarwangi, Galoeh Irdanella (Accounthink : Journal of Accounting and Finance, 2024)
Financial products are becoming more varied and common. The proliferation of financial products requires consumers to choose their assets with greater logic and analysis. The capacity to use different financial skills, such as essential money management (budgeting, spending, savings, loans, and credit), financial planning, and investment knowledge, is also equally important in making investment decisions. Factors that influence investment decisions are financial literacy and risk tolerance. This research aims to determine the influence of financial literacy on investment decision-making and to determine risk tolerance for investment decision-making among PNS working in Jakarta. The theories used by researchers are behavioral financial theory and modern portfolio theory. The method used in this research is quantitative, using a questionnaire distributed to target respondents. The analysis technique used is PLS-SEM. The research results state that (1) Financial knowledge has negative results and does not have a significant effect with a p-value of 0.080 > 0.05, (2) Financial attitude has positive results and has a significant effect with a p-value of 0.01 < 0.05, (3) Financial behavior has negative results and has a significant effect with a p-value of 0.035 < 0.05 and (4) Risk tolerance has positive results and has a significant effect with a p-value of 0.050 = 0.05.